Cluster development of industrial sector of russian economy - A. E. Miller (Вестник СибАДИ, 2017)
The article dwells upon the peculiarities of cluster development of industrial sector of economy. The author has justified a relational approach to providing a sustainable development of industrial clusters. There is offered a system and sequential approach to stimulation of forming territorial clusters and centers of cluster development in regions of Russia.